V-SITES: DEVELOPING A WEB-BASED BIOLOGY LEARNING MEDIA TO ENHANCE CONCEPTUAL UNDERSTANDING OF VIRUS IN SENIOR HIGH SCHOOL - Novantrya Salidar; Elfa Oprasmani; Dios Sarkity (Universitas Bhinneka PGRI, 2026)
This study aimed to develop Google Sites–based biology learning media on the topic of virus for Grade X students in alignment with the implementation of the Merdeka Curriculum. The research employed a Research and Development (RD) approach using the ADDIE instructional design model. The participants consisted of 40 students from a senior high school in Tanjungpinang. Data were collected through expert validation of content and media design, questionnaires to examine teacher and student responses, and pretest–posttest assessments to evaluate learning outcomes. The resulting product, named V-Sites, was structured into learning units consistent with the Merdeka Curriculum and designed to support independent learning by integrating instructional materials, learning activities, and assessment components within a single digital platform. The findings indicated that V-Sites achieved a very high level of validity based on expert evaluation and received positive responses from students. In addition, student learning outcomes improved significantly, as reflected by an N-Gain score of 0.76 (high category). These results demonstrate that Google Sites–based learning media are effective and appropriate as a digital alternative for teaching virus material in Grade X biology.